1995
DOI: 10.1152/ajpcell.1995.268.3.c596
|View full text |Cite
|
Sign up to set email alerts
|

Myosin phosphorylation enhances rate of force development in fast-twitch skeletal muscle

Abstract: Skeletal muscle force output is regulated through Ca(2+)-mediated alterations of the rate at which cross bridges make the transition from non-force-generating to force-generating states, defined by the rate constant fapp. In skinned-fiber models, phosphate incorporation by the regulatory light chain (R-LC) subunits of myosin increases fapp independent of Ca2+, thus increasing the Ca2+ sensitivity for the rate and extent of steady-state force development. The goal of this study was to determine whether phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 0 publications
3
48
0
2
Order By: Relevance
“…The mechanism of PAP, myosin regulatory light chain phosphorylation, is most pronounced immediately after muscle activity, and then declines (Houston and Grange 1990;Houston et al 1985;Vandenboom et al 1995). In response to relatively brief muscle activity, such as a 10-s MVC of the knee extensor muscles, the manifestation of the PAP mechanism, twitch potentiation, is also greatest immediately after the MVC and then declines exponentially (Folland et al 2008;Hamada et al 2000;Houston and Grange 1990;Rassier and Herzog 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of PAP, myosin regulatory light chain phosphorylation, is most pronounced immediately after muscle activity, and then declines (Houston and Grange 1990;Houston et al 1985;Vandenboom et al 1995). In response to relatively brief muscle activity, such as a 10-s MVC of the knee extensor muscles, the manifestation of the PAP mechanism, twitch potentiation, is also greatest immediately after the MVC and then declines exponentially (Folland et al 2008;Hamada et al 2000;Houston and Grange 1990;Rassier and Herzog 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The most common indicator of PAP is increased evoked isometric twitch force (twitch potentiation) observed following an evoked isometric tetanic contraction (O'Leary et al 1997) or a maximal voluntary isometric contraction (MVC) (Vandervoort et al 1983). More relevant to performance of fast movements is that PAP increases the rate of force development of evoked isometric tetanic contractions (Baudry and Duchateau 2007a;MacIntosh et al 2008;Vandenboom et al 1995), the force and power of evoked high velocity shortening (concentric) contractions (Abbate et al 2000), and the maximum velocity attained by evoked shortening contractions under load (Baudry and Duchateau 2007b;MacIntosh et al 2008). In addition to its effects on evoked (involuntary) contractions, PAP has been associated with enhanced voluntary contraction performance such as increased isometric rate of force development (Baudry and Duchateau 2007a), increased torque of moderately high velocity isokinetic concentric contractions (Miyamoto et al 2010), and increased shortening velocity attained with various loads (Baudry and Duchateau 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…The graphs (Figs 4 and 7) displaying the change in DT and DT tc-' during 10 Hz stimulation illustrate the similar pattern of change in these parameters among the various groups, and the apparent restoration of a control-type response in atrophied muscle treated with DS. Comparison of these graphs illustrates the importance of the rate of force development in effecting the staircase response (MacIntosh & Gardiner, 1987;Vandenboom, Grange & Houston, 1995). It is interesting to note that repetitive stimulation of TTX-treated muscle resulted in prolongation of tc (from 5 to 10 s) without corresponding enhancement of DT.…”
Section: Half-relaxation Timementioning
confidence: 93%
“…For example, work by Stull and colleagues showed that stimulation-induced elevations in the myosin phosphate content of rat hindlimb muscles correlated with the magnitude of PTP [22,26,29]. Subsequent studies have confirmed these associations in mouse and rabbit hindlimb muscle [30][31][32][45][46][47]. Perhaps the most compelling evidence that RLC phosphorylation is responsible for PTP comes from studies performed on mouse extensor digitorum longus (EDL) muscles devoid of the skeletal isoform of myosin light-chain kinase (skMLCK), the enzyme responsible for phosphorylating the RLC in mammalian skeletal muscle [40].…”
Section: Introductionmentioning
confidence: 98%